DIPG-57. A COMPREHENSIVE GENE/PROTEIN INVESTIGATION OF THE TUMOUR MICROENVIRONMENT IN DIFFUSE MIDLINE GLIOMA IN CHILDREN. Issue 2 (22nd June 2018) - Loveson, Katie; Fillmore, Helen
Abstract: Pediatric diffuse midline glioma (pDMG) is a rare aggressive childhood malignancy. While much is known concerning molecular genomics, our focus is on understanding the tumour microenvironment and how this influences cancer growth. We hope to learn how interaction and communication between host cells, tumour cells and extracellular matrix proteins (ECM) promote the pDMG growth. We conducted bioinformatic analysis using data obtained from R2: Genomics Analysis and Visualization Platform of pDMG tissue samples (GSE26576). In parallel, fixed-formalin paraffin embedded tissue (FFPE) was obtained from post-mortem brain. RNA was extracted from tumour core, adjacent and 'normal' tissue. Following quality control experiments to ensure RNA integrity, RNA was then used for a focused ECM array. Eighty ECM related genes were chosen for bioinformatics analyses to make indirect comparisons to the ECM focused RT2 profiler. Preliminary bioinformatic analyses indicate that 15 of the 80 genes were significantly up-regulated in pDMG tumours compared to normal brainstem (p<0.05). The most significantly differentially expressed include, Matrix Metalloproteinase1 (MMP1), Collagen type XI alpha 1 (COL11A1), and Matrix Metalloproteinase 16 (MMP16) (p<0.0001). In preliminary analyses of data obtained from FFPE tissue, tumour adjacent RNA was compared to 'normal' brain. Out of 80 genes, 7 were differentially expressed and include COL11A1, Collagen type VI alpha 2 (COL6A2) and Laminin alpha 3 (LAMA3). We believe that by identifying key host/tumour interactions that drive pDMG growth, this knowledge will help lead to improved therapeutics for this devastating childhood brain cancer.